Seropathological Diagnosis of Toxoplasma gondii in Stray Cats in Baghdad Province: Dhamraa, R. Jalil and Mohammed, J. Alwan - Alwan, mohammed J. (The Iraqi Journal of Veterinary Medicine, 2014)
The current study was performed an investigation in seropositive stray cats with Toxoplasma gondii and to correlate the results of pathological lesions with seropositive results of the cats. To achieve these goals, fifty blood samples and specimens from internal organs (liver, spleen, brain, kidney, intestine and lung) of stray cats were collected from different area of Baghdad Province during the period 1.10.2011-1.10.2012. Seropositive ELISA-IgG was demonstrated that 66 % of stray cats while female expressed (75 %) of seropositive ELISA-IgG were higher than male (30% ) and animals with average age 2months showed high percentage of seropositive ELISA-IgG (100%) as compared with age (adult cat) that expressed( 63.82 %) of seropositive. There was a significant difference (P≤0.01) among positive cases to anti-Toxoplasma ELISA-IgG. Severe pathological lesions were noticed in the lungs ,livers and intestines of animals that expressed high (optical density) (OD) of anti-Toxoplasma IgG ,in addition ,tachyzoits intracytoplasm of alveolar macrophages and hepatocytes as well as free zoites in alveolar space of the lung, were reported. Local necrosis with tachyzoites was seen in the brain of the cats, in addition to mineralization. On bases of the presence of pathological lesions in cats that expressed seropositive anti-Toxoplasma antibodies, it can be conclude that T.gondii is responsible for the appearance of inflammatory reaction in the internal organs of cats and there is a correlation between seropositive and pathological lesions of T.gondii infection and this parasite is highly distributed in Baghdad stray cats and it may be an important cause of abortion in the women.